Assessment of Employee Stock Option Plans’ Impact on the Financial Performance of Indian Construction & Infrastructure Companies - Rastogi, Amarnath (Stallion Journal for Multidisciplinary Associated Research Studies, 2023)
Organizations throughout the world continue to face enormous demands due to competitive pressures to increase productivity. Employee stock ownership plans (ESOPs), which boost the performance and productivity of the company and its workers by retaining them to a significant degree, have also been embraced in emerging countries like India in response to the competitive challenges with industrialized nations like the USA. Employee stock ownership plans are widely used by several successful and capable businesses worldwide. The growth of the firm's performance and employee productivity may be partly blamed for the success of ESOP enterprises in nations like the USA, Japan, and the UK, among others. In recent years, these consequences have drawn increased attention from all across the globe. This paper is an empirical investigation on the effects of ESOP on the financial performance of 10 publicly traded Indian construction and infrastructure enterprises over a six-year period. Based on secondary data gathered from business annual reports of the relevant years, the research evaluates three years before to and after the introduction of ESOPs for the chosen firms. Company-wise in the chosen selection, pre- and post-ESOP adoption analysis and regression analysis are performed.